Development of Learning Opportunities at Malaysian Universities Through Interpersonal Communication Among Students From Different Cultures and Nationalities - Sarwari, Abdul Qahar; Ainol Haryati, Ibrahim; Nor Ashikin, Abdul Aziz (IIUM Press, 2014)
The process of daily interactions among students of different cultures and nationalities, and its effects on increase of educational opportunities at the modern universities are among the important issues to be evaluated. This study was conducted to examine the process of daily interactions among local and international students of University Malaysia Pahang (UMP) and to find out whether this process has effects on enhancement of educational opportunities and collaborative learning at the university. A quantitative survey with its 220 participants from both local and international students of UMP was conducted as the main method of this study, and the qualitative interviews were done to enrich the data. Based on their personal agreements, from survey participants, 12 of them were participated in the qualitative interviews. The results of this study confirmed that interpersonal communication among students of different cultures and nationalities had positive effects on their university related life and paved the ways for them to have more collaborative activities at the university. However, findings of this study may encourage university students to have more interactions with their peers from different nationalities and have more academic achievements. University officials can pave the ways for students to have better opportunities for their daily interactions with their counterparts from different cultures. Further studies on the related issues may deepen the information and highlight more essential points.